Avaliação da correlação entre os parâmetros, carbono orgânico total e elementos tóxicos, em solo de um posto de serviço e revenda de combustíveis - Coelho, Eduardo Philipp Medeiros (2011)
Today a major responsibility for the contamination of soil and groundwater and surface water are establishments known as gas stations of fuel which has attracted increasing attention from both the general population as the state agencies of environmental control due to leaks in storage tanks and mainly to disruption of pipe corrosion of tanks and pumping. Other services, like oil changes and car wash are also causes for concern in this type of establishment. These leaks can cause or waste produced, and the contamination of aquifers, serious health problems and public safety, since most of these stations located in urban areas. Based on this, the work was to evaluate soil contamination of a particular service station and fuel sales in the city of Natal, through the quantification of heavy metals like Cd, Cu, Cr, Ni, Pb, Zn of total organic carbon (TOC) and organic matter using different techniques such as optical emission spectrometry with inductively coupled plasma source (ICP OES), Total Organic Carbon analyzer and gravimetric analysis respectively. And also to characterize the soil through particle size analysis. Samples were taken in 21 georeferenced points and collected in the same period. The soils sampled in sampling stations P3, P5, P6, P10, P11, P12, P13, P14, P15, P17, P18 and P20 showed the smallest size fractions ranging from fine sand to medium sand. The other study sites ranged from fine sand to medium sand, except the point P8 showed that only the type size medium sand and P19, indicating a particle size of the coarse type. The small correlation of organic matter with the elements studied in this work suggests that these are not of anthropogenic origin but geochemical support